Baobab pulp authenticity and quality control by multi-imaging high-performance thin-layer chromatography. (1st October 2022) - Chepngeno, Joyce; Imathiu, Samwel; Owino, Willis O.; Morlock, Gertrud E.
Highlights: Method for detecting adulteration of baobab fruit pulp samples was developed. Efficiency and effectiveness of the method in resource utilization was excellent. Cereal-fruit pulp adulteration was detected from 10% upwards, depending on adulterant. Characteristic sample patterns based on plant origin were established with the same method. Raffinose was identified as a marker of cereal-based adulteration in baobab fruit pulp. Abstract: Globalization of trade and increasing demand for baobab fruit pulp powder ( Adansonia digitata ) has led to more adulteration incidence with physically similar products, e.g. sifted cereal flours. In this study, 135 baobab samples drawn from trees in Kitui and Kilifi (Kenya) and North and South Kordofan (Sudan) were used as the reference and compared with adulterated (with 10–30% sifted rice, maize and wheat flours) baobab samples using multi-imaging by high-performance thin-layer chromatography. The ethanol – water extracts were separated on a normal phase. Any differences were detected via multi-imaging (UV/Vis/FLD) including diphenylamine alanine o -phosphoric acid, p -anisaldehyde sulfuric acid and p -amino benzoic acid reagents. Raffinose was identified as a marker compound for cereal-based adulteration. The method accuracy (recovery of 95%) and detection from 10–30% flour addition onwards are sufficient to curb economically motivated adulteration, to control product quality and to ensure consumer protection for local and international trade.